Efficacy and safety of simultaneous integrated boost intensity-modulated radiotherapy combined with temozolomide for the postoperative chemotherapy treatment of multifocal high-grade glioma - Jiang, Nan; Xu, Li-ping; Li, Fei; Wang, Pei-pei; Cao, Yuandong (Frontiers in Oncology, 2025)
BackgroundThe multifocal manifestation of high-grade glioma is a rare disease with an unfavorable prognosis. The pathogenesis of multifocal gliomas and pathophysiological differences in unifocal gliomas are not fully understood. The optimal treatment for patients with multifocal high-grade glioma is not defined in the current guidelines; therefore, individual case series may be helpful as guidance for clinical decision-making.MethodsPatients with multifocal high-grade glioma treated with simultaneous integrated boost intensity-modulated radiotherapy combined with temozolomide for postoperative treatment at our institution between January 2020 and December 2023 were retrospectively analyzed. Multifocality was neuroradiologically assessed and defined as at least two independent contrast-enhancing foci in the MRI T1 contrast-enhanced sequence. Overall and progression-free survival were calculated from the diagnosis until death and from the start of radiation therapy until the diagnosis of disease progression on MRI for all patients.ResultsA total of 42 patients with multifocal high-grade glioma were examined, of which 16 were female and 26 were male. The median age of all patients was 57 years (range: 23–77 years). The median KPS score was 80 (range: 50–100). Complete resection was performed in 10 cases, and partial resection was performed in 32 cases before the start of radiation therapy. The prescription schedule was 54 Gy (1.8 Gy × 30) with an SIB of 60 Gy (2 Gy × 30). Concomitant temozolomide chemotherapy was administered to 40 patients. Median survival was 19 months (95% CI 14.1–23.8 months) and median progression free survival after initiation of RT 13 months (95% CI 9.2–16.7 months). Five patients experienced grade 3 toxicity, none experienced grade 4 toxicity, and no treatment-related deaths occurred.ConclusionMultifocal high-grade gliomas can be treated safely and efficiently with simultaneous integrated boost intensity-modulated radiotherapy with concomitant and adjuvant TMZ chemotherapy.